Screw thread motility of polarly flagellated bacteria enhances movement through structured environments - Kühn, Marco Julian; Justus Liebig University Giessen (My University, 2019)
Many bacteria from diverse habitats are motile by means of flagella, long helical protein filaments that are rotated by a complex motor embedded in the cell envelope. Although flagella are often associated with swimming in aquatic environments, they can also mediate movement in viscous media or structured environments like soil, mucus or tissue. Generally, bacteria with multiple flagella are considered to be better equipped for movement in structured environments because they can generate more torque. On the other hand, bacteria that possess a single filament, usually at the cell pole, are generally considered to be adapted for fast swimming in bulk liquids. This might be valid as a basic scheme, but many bacteria are subject to different or changing environments that pose distinct demands on the motility apparatus. Hence, motile bacteria need strategies to manage various, distinct environmental conditions.The findings presented in this thesis show that even a single polar flagellum can be adapted for both robust free swimming in bulk liquid as well as efficient movement through structured environments. This is achieved by balancing the properties of the flagellar filament to allow a certain degree of instability when the load on the filament increases due to increasing viscous drag, while still providing enough stability for regular swimming in aqueous conditions. Many marine bacteria, such as our model organism Shewanella putrefaciens, can swim forwards or backwards depending on the direction of motor rotation, and turn by a run-reverse-flick mechanism. High-speed microscopy of swimming cells with fluorescently labelled flagellar filaments in a structured environment revealed that this regular swimming behaviour is often not sufficient to back out from dead ends or to squeeze through narrow passages. Instead, S. putrefaciens was found to wrap its flagellar filament around its cell body, resembling a screw thread, and move between agarose patch and glass surface in a screw-like fashion without slip of the flagellar helix. This behaviour is triggered by an instability at the base of the filament when the motor rotates in backward direction and the viscous drag-induced torsional forces exceed the stability of the filament, which is therefore trying to invert the handedness of the helix.The filament of S. putrefaciens is composed of two different flagellin subunits: FlaA, which forms a short segment at the base of the filament, and FlaB, which forms the remaining, major segment of the filament. This segmentation is most likely achieved by a temporal control of flagellin transcription with flaA being transcribed before flaB. Thus, FlaA is produced and exported first and forms the basal segment. Genetically modified strains that produce full-length filaments only consisting of either FlaA or FlaB showed impaired movement performance in either structured environments or under free-swimming conditions, respectively. Particularly, FlaB-only mutants showed strongly increased frequency of screw thread formation while FlaA-only mutants showed no screw thread formation at all. Thus, introducing the FlaA segment with its distinct properties stabilises the flagellar filament and balances screw thread formation. Holographic microscopy, population-wide motility assays and numerical simulations of wild-type and mutant cells suggested that the wild-type filament is a trade-off between swimming efficiency and the ability to switch to the screw thread motility mode. Hence, wild-type cells are well-equipped for motility in a wide range of conditions, both for swimming in bulk liquid as well as for screw-like movement in structured environments. Furthermore, the wild type forms a heterogeneous population of cells that differ in the length of the FlaA segment. Therefore, subpopulations of cells are more likely to switch to screw thread mode than others, but a fraction of the population will always be well-equipped for movement in a specific environment.The mechanisms of screw thread formation is fundamental and potentially applies to many polarly flagellated bacteria. This is supported by recent findings of the screw thread motility mode in more species, all of them being polarly flagellated but having varying numbers of flagellar filaments. Building the filament from more than one flagellin modifies its properties and can affect all aspects of flagella-mediated motility, which might explain why about half of all flagellated bacteria possess more than one flagellin gene. The ability to wrap the filament around the cell body under high-load conditions provides a motility mode for more efficient movement in structured environments. This potentially facilitates navigation in various habitats like marine sediment, soil or other porous media, polysaccharides and mucus, as well as viscous or constricted passages in animal hosts. Possibly, movement through a biofilm matrix might also be facilitated.
Keywords: Shewanella; flagella; motility; structured environment; bacterial screw thread; ddc:570